A poesia nos livros didáticos : contribuição para um projeto educativo emancipatório - Senna, Miguel Angelo Braga (2014)
This study aims at analyzing poems transcribed in high-school coursebooks adopted in public schools since 2012, the study done by works about the poems, the works’ content related to poetry and literature and the work developed by the teachers with these poems in their classes, in order to verify destabilizing potential concerning students’ guidance in terms of social exclusion in agreement to ideology of an Emancipating Educational Project proposed by Boaventura de Sousa Santos. This study is founded on “critical method” by Bloch, and its analyses have both quantitative and qualitative features. The data on teachers were gathered through semistructured interview. It was possible to see that the poems, in general, in both publications appear in large amounts, but small number. This happens if we consider those approaching inequality and social exclusion situations; those which are fragile in terms analyses the books make, with poor or nonexistent exploration of the textual sense, which hinders a critical and education task with students; those in which the poetry and literature content are fragmented and loose in the coursebooks, which compromises students' general understanding. Also, it is seen that there overall considerable work of teachers on poems in the coursebooks so as to guide students towards social reality. We concluded that despite in the given inconsistencies in poems and coursebooks, if teachers — as suggested by Dalvi — face coursebooks as space for sketching, building new views about its content in order to "cheat" the way the book "cheats", they can make it more accessible and educational to students. In sum, the potential of coursebook poetry and the possibilities of teachers point towards the feasible task of showing students the inequality and exclusion situations of the past in order to destabilize them in the present, in compliance with the idea of the Project mentioned above.